MySQL Pocket Reference - Reese, George (O'Reilly, 2011)
Easy to take and use anywhere, the MySQL Pocket Reference provides instant reminders on how to use important MySQL functions in conjunction with key parts of the LAMP open source infrastructure. The book covers installation of MySQL and includes a description of SQL commands, data types, operators, and functions. In this small book, you get a handy reference to the enormous feature set of MySQL, the dominant database in the open source world.